President's Annual Report, 1957-1958 - Thaxton, J. Ralph, Dr. (Valdosta State University Archives and Special Collections, 1958)
Annual report to the Chancellor of the University System of Georgia. Summarizes activity in faculty hiring, firing, and resignations. Also mentions faculty that are taking graduate coursework. Provides information on average faculty pay for full Professors, Associate Professors, Assistant Professors, and Instructors. Tables provide information such as faculty teaching loads, student courseloads, enrollment, degrees conferred, and enrollment by county. Additional tables include data on student scholarship, student exclusions, probations, and Dean's List. Student activity in Greek Life is also discussed, including newly formed chapters. Extracurricular activities for the year, including sports, are summarized. New curricula and library activity are mentioned, along with an appended Report of the Librarian, which discusses expenditures, projects and circulation. New constructions and gifts to the university are discussed.
Keywords: Valdosta State University; College publications; Corporate reports; College presidents